Development Toward Digital Marketing On Cincai Cafe & Coffee Social Media Platform - Estefania Estefania; Wisnu Yuwono (ConCEPt - Conference on Community Engagement Project, 2023)
The impact of the COVID-19 pandemic has affected and changed almost all people's lifestyles between the sectors affected from the economy and tourism where’s coffee shops is include too. Even when conditions are severe, the government requires owners to temporarily close their businesses for a certain period at a time. So every business must find alternatives and adapt to this pandemic situation, one of the way is digital marketing, where entrepreneurs can communicate indirectly with potential customers and regular customers through social media, besides that, using the right language and attractive promotions will be one of the added values to attract consumers attention. This development will helps in increasing social media interactions such as building a good image & awareness in the eyes of customers, expanding the reach of customers, increasing income and customer satisfaction with reducing the distribution or promotion costs. The result of this implementation are expected to be a solution to Cincai Cafe and Coffee business operation.